2004
DOI: 10.1111/j.1365-2796.2004.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low‐density lipoprotein in plasma is a prognostic marker of subclinical atherosclerosis development in clinically healthy men

Abstract: Objective. To investigate the association between plasma oxidized low-density lipoprotein (OxLDL) and the progress of clinically silent atherosclerosis, as measured by ultrasound in the carotid arteries. Design. Prospective, observational study with more than 3 years of follow-up. Setting. One-centre study at university hospital. Material and methods. The subjects (n ¼ 326) were obtained by stratified sampling from a population sample of men who were 58 years old at baseline. Carotid artery intima-media thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 28 publications
4
56
0
12
Order By: Relevance
“…In a prospective study, Shimada et al (114) observed 238 patients with CAD for a mean of 52 mo and showed that baseline levels of OxLDL-DLH3 were significantly higher in patients with the subsequent development of cardiac death, nonfatal myocardial infarction, and unstable angina. In a prospective study, Wallenfeldt et al (115) showed that baseline OxLDL-4E6 levels predicted the progression of carotid artery intimamedia thickness in asymptomatic and presumably healthy 58-y-old Swedish men, independent of other cardiovascular risk factors. In summary, OxLDL may serve as an attractive biomarker because it may provide a link between lipoprotein disorders and inflammation.…”
Section: Lipid Markersmentioning
confidence: 99%
“…In a prospective study, Shimada et al (114) observed 238 patients with CAD for a mean of 52 mo and showed that baseline levels of OxLDL-DLH3 were significantly higher in patients with the subsequent development of cardiac death, nonfatal myocardial infarction, and unstable angina. In a prospective study, Wallenfeldt et al (115) showed that baseline OxLDL-4E6 levels predicted the progression of carotid artery intimamedia thickness in asymptomatic and presumably healthy 58-y-old Swedish men, independent of other cardiovascular risk factors. In summary, OxLDL may serve as an attractive biomarker because it may provide a link between lipoprotein disorders and inflammation.…”
Section: Lipid Markersmentioning
confidence: 99%
“…PM induces highdensity lipoprotein (HDL) dysfunction with loss of its anti-inflammatory properties (Araujo and Nel 2009). Oxidative transformation of LDL into ox-LDL is a key step in the initiation and progression of atherosclerosis (Stocker and Keaney 2004), and circulating levels of ox-LDL are therefore an early marker, and a risk factor for the disease (Wallenfeldt et al 2004). The correlation between PM exposure and circulating levels of ox-LDL on an individual level was shown by Jacobs et al, demonstrating a dose-dependent association between this parameter and the carbon load of airway macrophages, a personal marker for chronic exposure to fossil fuel derived ultrafine particles (Jacobs et al 2011).…”
Section: Chronic Pm Exposure and Atherosclerosismentioning
confidence: 99%
“…Interestingly, several studies have demonstrated that increased plasma oxLDL concentration is associated with the metabolic syndrome (45)(46)(47)(48). Although the actual extent of in vivo interactions between adipose tissue and lipoproteins is still to be defined, a bulk of data suggests that adipocytes could have a role in the metabolism of circulating lipoproteins including oxLDL.…”
mentioning
confidence: 99%